Teaching Back Health in the School Setting: A Systematic Review of Randomized Controlled Trials - Miñana-Signes, Vicente (Int J Environ Res Public Health, 2021)
School-based interventions have reported effectiveness on back health; however, there are no specific guidelines for teaching body mechanics and posture in primary and secondary schools. To identify, describe, and analyze the educative features of randomized controlled trials (RCTs) on back health developed to date in the school setting, a systematic review was performed following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) recommendations. RCTs exclusively focused on educational setting electronic databases included PubMed, EMBASE, PEDro, Web of Science, SPORTDiscus, ERIC, and MEDLINE on the Ovid platform. Databases were searched for potentially eligible studies from the earliest date up to 18th March 2020. A total of 584 records were obtained from the database searches. A total of six articles that applied inclusion criteria were assessed for eligibility. All of these studies found improvements in postural habits and the level of knowledge with regard to back health, as well as a reduction in the prevalence of back pain. None of the studies used the student-centered method, and three studies used evaluation instruments with a pilot validation. Research on RCT interventions concerning back health in the school setting is scarce. None of the interventions applied a constructivist or student-centered method. The use of validated and standardized assessment instruments is required.